SpoofSentry: Email Spoofing Detection Tool Using Domain-Based Authentication - MOHD NAZLAN, NUR FATIN NAZIFA; DR. SITI FADZLUN BINTI MD SALLEH (Applied Information Technology And Computer Science, 2026)
Email spoofing poses a significant cybersecurity threat, leading to phishing attacks and business email compromise with billions in global losses. This project develops SpoofSentry, a comprehensive Email Spoofing Detection Tool that integrates Sender Policy Framework (SPF), Domain Keys Identified Mail (DKIM), and Domain-based Message Authentication, Reporting and Conformance (DMARC) with Random Forest machine learning for enhanced threat detection accuracy. The desktop application features hybrid analysis combining traditional authentication verification with intelligent pattern recognition, automated threat classification, and alert systems. The tool provides user-friendly interfaces for single email analysis and bulk processing, with automatic whitelist and blacklist management and reporting capabilities. Testing demonstrates effectiveness in identifying sophisticated spoofing, enabling organizations to implement enterprise-level email security without extensive technical expertise.